Simulation of Railroad Doors using Combinational Logic Concepts - Faisal Muttaqin; Fetty Tri Anggraeny; Mahardika Virgo Wuryantoro; Rangga Widiasmara; Abdul Aziz Naufal Farizqi; Ahmad Sofian Aris S; Rafie Ishaq Maulana (Nusantara Science and Technology Proceedings, 2022)
We use computers to help solve various problems in our daily life. From a simple sensor circuit to a very complex supercomputer, a computer can be found. As the name suggests, computers compute something and produce a value that then can be taken advantage of. The problem is that computers do not simply understand human language. Our world works with the “continuous” concept, as opposed to the “digital” concept that computers use. Digital system uses some discrete and exact value. Computers use two discrete and exact value, which is 0 and 1. This is more commonly known as a binary system. This system, combined with mathematical logic, is the very core of every computer. Thus, it is needed to convert our problems into a binary system that computers can understand. An example of this is sensors that can be found in various systems like automatic train passing or automatic hand dryers. Most sensors only work between two states, that is ON and OFF, LOW and HIGH, or detecting and not detecting. In this paper, we are going to create a system that manages an automatic train crossing. The system should be able to correctly open or close the train gate based on the presence of a train. It means the train gate should only be closed when a train is passing, and not something else. Some sensors are already installed that can detect if a train is in front of them or not. This system uses the concept of combinational logic as the concept of sequential logic alone would not be able to store the state of a train crossing. Thus, memory elements like flip-flops are also required in this system.